RESPONS GEREJA TERHADAP KEMISKINAN DAN KESENJANGAN EKONOMI DALAM KONTEKS MASYARAKAT PERTANIAN INDONESIA - Eder Timanta Sitepu (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2026)
This study explores social inequality within the church in the context of agricultural communities as a result of poverty, economic disparity, and corruption. Data from the Central Bureau of Statistics (BPS) indicates that most farmers in rural areas remain vulnerable and far from prosperous. The inequality is driven by limited land ownership, unstable commodity prices, and economic policies that disadvantage farmers. As part of society, the church is called to take an active role through the spirituality of simplicity (ugahari), community empowerment, and the management of economic resources such as credit unions. The study concludes that poverty alleviation is not only the responsibility of the government but also a moral obligation of the church to promote social justice and collective well-being.